Three new species of Entomobrya from Poland (Collembola, Entomobryidae) - Furgoł, Michał (Zootaxa, 2017)
A rich material of springtails from Poland was analysed using chaetotaxy. The analysis of the genus Entomobrya reaveled three new species, which are described in this paper: E. emiliae sp. nov., E. flavovirens sp. nov., and E. kasprowiensis sp. nov. Both the modern (pattern of macrochaetotaxy) and the traditional (colouration) characters were applied in the descriptions.